The Influence of Islamic Boarding Schools for Young People in the Era of Globalization - Faisal Tamimi (Yayasan Zia Salsabila, 2024)
Indonesia is a country where the majority of the population is Muslim. One method of Islamic religious education in Indonesia is education in Islamic boarding schools. These Islamic boarding schools themselves are spread throughout almost all of Indonesia. Islamic boarding schools function to educate the younger generation who have a deep religious understanding, noble morals, and the ability to make positive contributions to society. This research uses library research which relies on bibliographies from articles and books. The results of this research show that Islamic boarding schools contribute to efforts to help people in need in various regions of the world, including responding to natural disasters and humanitarian aid. The influence of the young Muslim generation in the era of globalization depends on the perspective, values and personal commitment of each individual. They can become agents of positive change in facing challenges and opportunities in the era of globalization, and play an important role in understanding and implementing Islamic values in an increasingly globally connected world.